EVALUASI PELAKSANAAN PENDAFTARAN TANAH SISTEMASTIS LENGKAP DI KECAMATAN TUMPAAN KABUPATEN MINAHASA SELATAN - Peggye Lenda Olivia Rembeth; Bobby Jhon Vian Polii; Leonardus Ricky Rengkung (AGRI-SOSIOEKONOMI, 2020)
This study aims to determine the evaluation of the complete systematic land registration program (PTSL) in Tumpaan District, South Minahasa Regency. The research was conducted from February to June 2020. The data sources in this study used primary and secondary data. Primary data is through direct interviews with implementers and participants. The number of respondents was 4 authorized officers and 21 participants in complete systematic land registration in 2017. Secondary data is data obtained through related agencies in this study. The data analysis used in this research is descriptive qualitative analysis. The results showed that the Complete Systematic Land Registration Activity in Tumpaan District, South Minahasa Regency has been running according to the activity stages. There were 18 or 85.71% of respondents who considered the implementation of PTSL activities in the good category, while 3 people or 14.28% considered it very good. The response to the counseling carried out by the National Land Agency Office of South Minahasa Regency, there were 2 people or 9.52% of respondents who said they did not understand the counseling delivered, while 19 respondents or as much as 90.47% said they understood the counseling about PTSL that was delivered. There were 7 people or 33.33% of the total respondents who felt very profitable about the existence of this PTSL program while 14 people or 66.66% of respondents felt the PTSL program was for them. 10 respondents or 47.61% of the total respondents did not experience difficulties in the process of managing PTSL, while 11 respondents or 52.38% had difficulties where the completeness of the files and data they had did not meet the requirements.*eprm*